Two Cases of Pituitary Stalk Interruption Syndrome in Syrian Children - Ibrahim Alali; Reem Saad; Younes Kabalan (Case Reports in Endocrinology)
Pituitary stalk interruption syndrome (PSIS) is an extremely rare cause of growth failure and delayed puberty. It can be diagnosed by magnetic resonance imaging (MRI) of the hypothalamus and pituitary gland, showing an ectopic or absent posterior pituitary, an absent or interrupted pituitary stalk, or small anterior pituitary, in combination with growth hormone or other pituitary hormone deficiencies. The exact etiology of PSIS is unknown. In this article, we describe two cases of PSIS in Syria which are, as far as we know, the first published cases.